The Use of Web-Based Technologies in Health Research Participation: Qualitative Study of Consumer and Researcher Experiences - Pang, Patrick Cheong-Iao; Chang, Shanton; Verspoor, Karin; Clavisi, Ornella (Journal of medical Internet research, 2018)
Health consumers are often targeted for their involvement in health research including randomized controlled trials, focus groups, interviews, and surveys. However, as reported by many studies, recruitment and engagement of consumers in academic research remains challenging. In addition, there is scarce literature describing what consumers look for and want to achieve by participating in research. Understanding and responding to the needs of consumers is crucial to the success of health research projects. In this study, we aim to understand consumers' needs and investigate the opportunities for addressing these needs with Web-based technologies, particularly in the use of Web-based research registers and social networking sites (SNSs). We undertook a qualitative approach, interviewing both consumer and medical researchers in this study. With the help from an Australian-based organization supporting people with musculoskeletal conditions, we successfully interviewed 23 consumers and 10 researchers. All interviews were transcribed and analyzed with thematic analysis methodology. Data collection was stopped after the data themes reached saturation. We found that consumers perceive research as a learning opportunity and, therefore, expect high research transparency and regular updates. They also consider the sources of the information about research projects, the trust between consumers and researchers, and the mobility of consumers before participating in any research. Researchers need to be aware of such needs when designing a campaign for recruitment for their studies. On the other hand, researchers have attempted to establish a rapport with consumer participants, design research for consumers' needs, and use technologies to reach out to consumers. A systematic approach to integrating a variety of technologies is needed. On the basis of the feedback from both consumers and researchers, we propose 3 future directions to use Web-based technologies for addressing consumers' needs and engaging with consumers in health research: (1) researchers can make use of consumer registers and Web-based research portals, (2) SNSs and new media should be frequently used as an aid, and (3) new technologies should be adopted to remotely collect data and reduce administrative work for obtaining consumers' consent.